Evaluation of Colonization and Biofilm Formation of E. faecalis over G-MTA, W-MTA and Biodentine. In vitro study - Ruiz-Flores, Alejandra (2025)
Apicectomy is a procedure indicated for the treatment of non-healing apical periodontitis after non-surgical Root Canal Treatment or certain clinical conditions; the procedure consists in the elimination of the last 3 mm of the RCS and creation of an apical preparation to finally seal it with a root-end filling material, like bioceramics. It has been reported that bioceramic materials (Gray-MTA, White-MTA and Biodentine) have adequate antibacterial properties. The aim of the study is to evaluate the colonization capacity and biofilm formation of E. faecalis over the surface of bioceramic materials In vitro. 180 dentin disks were employed and distributed in 3 experimental groups (G-MTA+E. faecalis, W-MTA E. faecalis and Biodentine+E. faecalis) and 3 control groups (G-MTA, W-MTA and Biodentine), the surface area covered by biofilm and microorganisms were evaluated by SEM. All samples of experimental groups showed a rough and irregular surface due to microorganism colonization and biofilm formation. G-MTA group showed better antimicrobial properties than W-MTA and Biodentine. The complete elimination and removal of damaged and contaminated periapical tissues during the surgical treatment is critical for long-term success.